Coherence analysis of peripheral blood flow signals is a potential method for evaluating autonomic nervous system function - Lyu, Qiuyue; Qin, Yuning; Wang, Xin; Wang, Qizhen; Liu, Qi; Tu, Na; Liu, Yuhan; Huo, Zixin; Song, Xiaojing; Wang, Shuyou; Zhang, Weibo; Cao, Xue; et al. (Frontiers in Physiology, 2025)
IntroductionThe autonomic nervous system (ANS) is crucial for maintaining homeostasis in the body and plays an important role in cardiovascular diseases. Although heart rate variability (HRV) is a commonly used non-invasive clinical tool to evaluate the function of ANS, it mainly reflects cardiac activity, and it is difficult to comprehensively capture the functional information of peripheral vascular regulation of ANS.MethodsThis study explored the feasibility of using peripheral blood flow signals to evaluate the function of ANS. The ANS function of healthy subjects was artificially intervened by giving glucose solutions at different temperatures. Subsequently, the correlation between peripheral blood flow signals and HRV was further explored. Finally, the quantitative relationship was verified by using an independent dataset.ResultsCoherence analysis shows that within a specific frequency band, the peak values of peripheral blood flow signals are significantly correlated with HRV.DiscussionThis study shows that peripheral blood flow signals analysis provides a new non-invasive way to evaluate the function of ANS. This method not only complements the limitations of traditional HRV analysis, but also hopes to promote the construction of a more comprehensive and multi-dimensional ANS functional evaluation system.